2000
DOI: 10.1097/00000539-200002000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cerebral Blood Volume with Changes in Position in Awake and Anesthetized Subjects

Abstract: Near-infrared spectroscopy, a bedside technique, has been used to measure changes in cerebral blood volume in normal subjects. We have used the same technique in anesthetized patients and have shown that, when a patient is placed in the head up position, the decrease in cerebral blood volume is attenuated, relative to normal subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
1
30
1
Order By: Relevance
“…The head-down position causes an increase in ICP, CBF and CBV 18,19 and a decrease in carotid artery blood flow. 20,21 All of these factors can reduce cerebral perfusion pressure, which can have a detrimental effect on cerebral tissue oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…The head-down position causes an increase in ICP, CBF and CBV 18,19 and a decrease in carotid artery blood flow. 20,21 All of these factors can reduce cerebral perfusion pressure, which can have a detrimental effect on cerebral tissue oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the ICP of SR cattle in a 30 cm head-up position was lower than that of RR cattle without the head-up position. Lovell et al report that the reduction in cerebral blood volume might be caused by a reduction in the volume of the venous and/or capillary compartments; they also suggest that changes in cerebral blood volume are unlikely to be the result of an increase in the arterial compartment, because arterial blood pressure did not change during tilting in their experiments [12]. In the present study, we observed similar results in the changing ICPs of cattle depending on head position, but arterial blood pressure showed no significant changes between the two tested groups.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, the ICPs of cattle in the sternal recumbent position were significantly lower than those of cattle in the lateral recumbent position during anesthesia. Changes in posture are known to affect the ICPs of humans and dogs [3,12,13,18]. Shah reports that the extradural pressure was greatest in the supine position and least in the prone position in human patients, the mean pressure being 22.6, 14.8 and 2.2 cmH 2 O in the supine, lateral and prone positions, respectively [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations